Lack of Self-Efficacy and Resistance to Innovation Impact on Insufficient Learning Capabilities: Mediating the Role of Demotivation and Moderating the Role of Institutional Culture - Yan, Shao (Frontiers in Psychology, 2022)
Learning capabilities have been an essential element for the success of second language learners that needs regulators' and researchers' emphasis. Hence, the current research examines the role of lack of self-efficacy and resistance to innovation on the insufficient learning capabilities of second language students in China. The current study also examines the mediating role of demotivation among the linkage of lack of self-efficacy, resistance to innovation, and insufficient learning capabilities and explores the moderating role of institutional culture among demotivation and insufficient learning capabilities. The researchers have applied the questionnaires method to gather the data from selected students and employed the smart-PLS to assess the measurement and structural models. The results revealed that lack of self-efficacy and resistance to innovation has a significant and positive linkage with insufficient learning capabilities. The results also exposed that demotivation significantly mediates among lack of self-efficacy, resistance to innovation, and insufficient learning capabilities. The findings also explored that the institutional culture significantly moderates the linkage between demotivation and insufficient learning capabilities.